Stress models of depression - Vollmayr, Barbara; Henn, Fritz A. (Clinical neuroscience research, 2003)
In order to understand the molecular changes underlying major depression animal models are needed. The best animal model of depression simulates the etiology and replicates symptoms, course and treatment of human depression. This article reviews the two most valid and best established animal models of depression, learned helplessness and chronic mild stress. Both models use uncontrollable stress to induce depressive like behavior, both have excellent face validity and replicate anhedonia and anergia in analogy to loss of interest and pleasure, one of two essential features of depression. In addition, both models demonstrate a variety of less specific symptoms like changes in locomotion, impaired learning ability, sleep alterations, loss of weight and decrease of sexual behavior. Endocrine disturbances of major depression as hypercortisolemia and dexamethasone non-suppression are also simulated in the two animal models. Neurobiological changes accompanying the depressive like behavior include dynamic changes of the monoamine systems and several peptide systems including the opioid system. Behavioral and neurobiological changes can be renormalized in both models by antidepressant treatment, which adds predictive validity to these models.
Gesehen am 04.11.2020